Farmers’willingness to pay for the ecosystem services of organic farming a locality study in valikamam area of sri lanka - Sooriyakumar, K.; Sivashankar, S.; Sireeranhan, A. (APPLIED ECOLOGY AND ENVIRONMENTAL RESEARCH, 2019)
This study investigates the farmers’ willingness to pay for ecosystem services of organic farming in Valikamam area of Sri Lanka. Choice modeling employed indicates that farmers are willing to pay more for big reduction in nitrate leaching and soil quality improvement than biodiversity improvement. It indicates that farmers give more weight to the short term benefit than the long term sustainable benefit. Income and education level of farmers positively influence farmer’s willingness to pay for soil quality improvement and Biodiversity. Young farmers are willing to pay more for soil quality improvement than old farmers. It shows that young farmers are willing to invest more to develop the farms than old farmers as young farmer value economic objective more than old farmers do. Middle aged farmers are willing to pay more for biodiversity. As middle aged farmers value social actions, environment responsibility more than young farmers do and are willing to invest more than old farmers do, middle aged farmers are willing to pay more for biodiversity than other farmers. Increasing farmer’s income, organizing awareness programs on sustainable agriculture and providing subsidies could be the most effective ways to adopt organic farming in Valikamam.
Keywords: Biodiversity; Choice modeling; Conditional logit model; Nitrate leaching; Soil quality